2018
DOI: 10.1111/coa.13104
|View full text |Cite
|
Sign up to set email alerts
|

Patient‘s perspective on long‐term complications after superficial parotidectomy for benign lesions: Prospective analysis of a 2‐year follow‐up

Abstract: From patients' perspective, sensation loss posed the major subjective problem after superficial parotidectomy. Appearance of the scar, and fear of revision surgery impaired more than 50% of the patients in their daily life without significant improvement during the 2 years postoperatively. Although superficial parotidectomy is a highly standardized and safe procedure, limited parotidectomy for proven benign parotid salivary gland neoplasms is more likely to result in patients with minimal or no displeasing com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 18 publications
(84 reference statements)
4
29
0
7
Order By: Relevance
“…Only 23% of LT-study patients affirmed pain and painful sensations 12-16 years after surgery, 13.5% of them described the pain as "marginal", 9.5% of them as "slight" and "moderate", no one as "severe" or as "the worst problem". Wolber et al [7] and Nitzan et al [9] underlined our results by reporting an incidence of postoperative pain of 30-40% during a short follow-up. In accord with Kaya et al [10], we can consequently argue that pain is an important early complication following parotidectomy which improves in the long-term.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Only 23% of LT-study patients affirmed pain and painful sensations 12-16 years after surgery, 13.5% of them described the pain as "marginal", 9.5% of them as "slight" and "moderate", no one as "severe" or as "the worst problem". Wolber et al [7] and Nitzan et al [9] underlined our results by reporting an incidence of postoperative pain of 30-40% during a short follow-up. In accord with Kaya et al [10], we can consequently argue that pain is an important early complication following parotidectomy which improves in the long-term.…”
Section: Discussionsupporting
confidence: 67%
“…Key goal in parotid surgical approaches for treatment of benign lesions is not only to remove the entire tumour and to minimize morbidity but also to maintain patients' quality of life. However, only few studies address patients' perspective on complications and the related QoL [5,[7][8][9][11][12][13], but predominantly in a short followup after parotidectomy -usually 6 months or 1-2 years -and by using different symptom-specific QoL assessments. Beutner et al [8] reported no changes in QoL in 34 patients one year after superficial parotidectomy for benign diseases compared with preoperative answers using the EORTC QLQ-C30…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations